Current methodologies of creating material passports: A systematic literature review - Ioannis Markou; Derek Sinnott; Ken Thomas (Case Studies in Construction Materials)
Material Passports (MPs) have emerged as a crucial tool for promoting circularity and resource efficiency within the built environment, especially in light of the sector’s substantial environmental impact. They can enable better material tracking, resource recovery, and waste reduction throughout the lifecycle of a building. However, their widespread implementation faces several limitations that hinder their full potential. This study presents a Systematic Literature Review (SRL) aimed to explore the methodologies currently used to create MPs. Guided by Kitchenham’s [37] guidelines and enhanced by modified PRISMA processes, the SLR was conducted in three stages: Planning, Review Execution, and Reporting. Key steps included formulating research questions, defining search strategies (Scopus and Web of Science), and applying inclusion/exclusion criteria. An initial search yielded 549 papers (2019 –2024 ), reduced to 33 after rigorous screening. Snowballing approach used to identify relevant studies that might have not been included through the selection process. The final number of studies, that were included for further analysis was 40 . Thematic analysis identified 6 approaches of creating MPs, which were identified to be BIM-based, blockchain-based, platform-based, QR code/ RFID-based, and Level(s)-based approaches. Additionally, some studies identified key data requirements that will be included in Material Passports. Content analysis helped identified the benefits of using Material Passports and gap analysis highlighted the technological challenges and research gaps. The study identified several critical gaps, such as the static nature of MPs, which require substantial manual input and do not provide real-time updates to reflect changes in a building’s lifecycle. These limitations affect their ability to accurately track materials and maintain data integrity throughout the building's operational life. Additionally, a gap in the existing literature is highlighted in that there has been no comprehensive systematic literature review specifically focusing on the technological gaps with in current MP frameworks. In order to identify the technological gaps and to address these challenges, the study suggests the development of Dynamic Material Passports that incorporate advanced technologies like Artificial Intelligence for automated data collection, real-time updates, and seamless integration across digital platforms. The findings point to the necessity for future research to develop dynamic, automated MPs that enhance data accuracy, operational efficiency, and scalability, thereby facilitating broader adoption of circular economy principles in construction.